Evaluation of the clinical value of sodium examination in spot urine in patients presenting with acute heart failure while using SGLT2i – ‘‘SPOT HF STUDY’’ - Aslan, Onur; Demirci, Emre Emrah (The European Research Journal, 2023)
Objectives: Sodium measurement in spot urine provides important information about the adequacy of the initial dose in acute heart failure (AHF) patients using intravenous diuretic (IV) and makes a guiding contribution to the titration decision. It is not clear whether spot urine sodium measurement has the same clinical value as the effect of sodium-glucose cotransporter 2 inhibitor (SGLT2i) drugs on urinary electrolytes. Our aim in our study is to investigate the clinical value of sodium examination in spot urine in AHF patients while using SGLT2i. Methods: Our study was conducted retrospectively and single-centered. AHF patients, administered IV diuretics were included in the study. Patients who were using and were not using SGLT2i were examined in two groups. The 2nd and 6th-hour sodium values in spot urine were measured. Results: Patients using SGLT2i (n = 46) and not using it (n = 54) were included. The mean age was 69.91 ± 11.84 years and 47% were female. The standard deviation value for the sodium in spot urine in patients using SGLT2i was clearly high and its distribution was significantly higher. A weak correlation was found between the sodium value in spot urine and the 24-hour urine volume in this group. Hospitalization history within 1 month after discharge was found to be 39% in the group using SGLT2i, and 51% in the group that did not use it, and this difference was statistically significant. Conclusions: The measurement of sodium in spot urine does not seem to have the same clinical value in HF patients using SGLT2i. Its correlation with urine volume is also decreasing in this group.